Domestic Piety in Fourth Century Rome: A Relic Shrine beneath the Church of SS. Giovanni e Paolo - Munk, Ana (2009)
The late 4th century reliquary shrine found within the domus complex below the church of Ss. Giovanni e Paolo in Rome has already been noted in previous scholarship for the archeological and hagiographical problems this monument poses to scholarship. In the text that follows the main focus of inquiry are its owners--the wealthy and pious senator Pammachius and his wife Paulina who through their network of family and friends belonged to highest ranks of Christian patriciate in Rome. What was the function of this shrine within their household? What does it tell us about the domestic piety in Rome? Why did it remain an isolated example of a domestic shrine? Answers to some of these questions are found in the dynamic of domestic asceticism which was particularly strong in the social circle to which Pammachius and Paulina belonged. The thesis that has been put forward here is that the spread of house-bound piety resulted in building a shrine intended for ecclesia domestica, as Saint Jerome described such environment in the house of Pammachius’ cousin and their mutual friend, Marcella.
ENG